Emotions of Teachers at Virtual Learning Environments - Estrada Esquivel, Ana Luisa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The research presented is mixed. The objective was to describe the emotions generated in virtual contexts by teachers from educational institutions in Spanish-speaking countries. Data collection was through a questionnaire with a Likert-type scale. The sample consisted of 37 teachers from Spanish-speaking countries. The results showed the existence of positive, negative and ambiguous emotions. The emotions were generated by experiences and beliefs about themselves, their students and about technology. The importance of generating digital educational resources that allow identification and emotional management was concluded.